Juridical Analysis of the Effectiveness of Solid Medical Waste Management at the Health Center in Batam City - Wulandari, Frisca; Amboro, F. Yudhi Priyo; Seroja, Triana Dewi (Universitas Islam Lamongan, 2023)
Abstract An environment is a spatial unit consisting of all objects, energy sources, conditions, and living things whose behavior affects the continuity of life and human welfare and how this behavior relates to other living things. Medical waste is waste that has a greater influence on the emergence of infections because it contains pathogenic agents which have an impact on causing disease. With the problem of waste treatment, especially solid medical waste, especially during this pandemic, it is known that dealing with these problems requires a system that regulates and becomes a reference for achieving a standard of living and sustainable development. The Theory of Legal Effectiveness and Development Law Theory was used to analyze the implementation of this research. The method used in this study uses empirical juridical methods. The empirical legal research method is based on realities in the field through observations at 3 (three) Puskesmas in Batam City, namely Puskesmas Sekupang, Puskesmas Mentarau, and Puskesmas Sungai Langkai, which respectively are samples of the highest, medium and lowest total waste production within Dinas Kesehatan Kota Batam. Samples were taken by purposive sampling method.